Association of carotid atherosclerosis and peripheral artery disease in patients with type 2 diabetes: risk factors and biomarkers - E. A. Koroleva; R. S. Khapaev; A. P. Lykov; A. I. Korbut; V. V. Klimontov (Сахарный диабет)
BACKGROUND: Carotid atherosclerosis (CA) and lower extremity peripheral artery disease (PAD) is a common and potentially life-threatening comorbidity in diabetes.AIM: to determine risk factors and biomarkers of the association of CA and PAD in patients with type 2 diabetes.MATERIALS AND METHODS: A single-center cross-sectional comparative study was carried out. Three hundred ninety one patients with type 2 diabetes were included. Duplex ultrasound of carotid and low limb arteries, screening/monitoring of diabetic complications and associated diseases, and assessment of glycemic control, biochemical and coagulation parameters were performed. Factors involved in vascular wall remodeling, including calponin-1, relaxin, L-citrulline, matrix metalloproteinase-2 and -3, were measured in blood serum by ELISA.RESULTS: The signs of CA and PAD were observed in 330 and 187 patients respectively. In 178 patients, both CA and PAD were revealed. The risk of combined involvement of carotid and lower extremity arteries was higher in patients with diabetic retinopathy (OR=2.57, p<0.001), chronic kidney disease (OR=4.48, p<0.001), history of myocardial infarction (OR=5.09, p<0.001), coronary revascularization (OR=4.31, p<0.001) or cerebrovascular accident (OR=3.07, p<0.001). In ROC-analysis, age ≥65.5 years (OR=3.43, p<0.001), waist-to-hip ratio ≥0.967 (OR=3.01, p=0.001), diabetes duration ≥12.5 years (OR=3.7, p<0.001), duration of insulin therapy ≥4.5 years (OR=3.05, p<0.001), duration of arterial hypertension ≥16.5 years (OR=1.98, p=0.002), serum L-citrulline ≥68 µmol/l (OR=3.82, p=0.003), and mean amplitude of glucose excursions ≥3.72 mmol/l (OR=1.79, p=0.006) were the risk factors for atherosclerosis of two vascular beds. In multivariate logistic regression analysis, age, diabetes duration and waist-to-hip ratio were independent risk factors for association of CA and PAD (p=0.005, p=0.0003, and p=0.004 respectively).CONCLUSION: In subjects with type 2 diabetes, carotid and lower extremity atherosclerotic disease is associated with age, diabetes duration, abdominal obesity, microvascular and macrovascular complications, glucose variability, and high serum levels of L-citrulline.